2011
DOI: 10.1029/2011jc007056
|View full text |Cite
|
Sign up to set email alerts
|

Variability of chlorophyll associated with El Niño–Southern Oscillation and its possible biological feedback in the equatorial Pacific

Abstract: [1] The relationship between oceanic phytoplankton and climate variability has been given increasing attention with the accumulation of satellite-derived chlorophyll data over the past decade. Here we examine the dominant variability of phytoplankton and its associated tropical climate systems; in particular, the El Niño-Southern Oscillation (ENSO). The analysis, using 148 months of chlorophyll data, reveals that the first two leading modes of tropical chlorophyll anomalies are linked to the mature phase and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 45 publications
5
43
1
Order By: Relevance
“…These figures are almost identical to Fig. 7a-f in Park et al (2011) despite the use of newly updated ocean color products and an extended data period. The leading chlorophyll pattern at zero lag shows negative anomalies in the equatorial Pacific (Fig.…”
Section: Impact Of Bio-physical Feedbacks 1815supporting
confidence: 72%
See 1 more Smart Citation
“…These figures are almost identical to Fig. 7a-f in Park et al (2011) despite the use of newly updated ocean color products and an extended data period. The leading chlorophyll pattern at zero lag shows negative anomalies in the equatorial Pacific (Fig.…”
Section: Impact Of Bio-physical Feedbacks 1815supporting
confidence: 72%
“…In order to further evaluate the performance of the biogeochemical model, the dominant modes of chlorophyll and associated SST patterns are analyzed from both model and observations. Previous studies reported that the first and the second mode of chlorophyll in the tropical Pacific are associated with the mature and decaying phases of ENSO cycle, respectively (Yoder and Kennelly 2003;Runge et al 2006;Park et al 2011). Figure 2a-f are the spatial patterns of observed chlorophyll and SST, respectively, regressed onto the first principle components (PC) of tropical chlorophyll at 3 different time-lags.…”
Section: Impact Of Bio-physical Feedbacks 1815mentioning
confidence: 99%
“…Al though the exact mechanism is unknown, El Niño events are known to influence regional trade winds (Cao et al 2007) and cyclonic activity (Chu & Wang 1997), which can influence ocean currents and thus recruitment dynamics. El Niño events are also typically associated with a decrease in primary production (Kahru & Mitchell 2000, Lo-Yat et al 2011, Park et al 2011; however, our data showed no correlation between ONI and chl a concentration (R 2 < 0.0001, p = 0.9717). Further investigation into ENSO and fish recruitment is warranted.…”
Section: Discussioncontrasting
confidence: 52%
“…As the main cycle of ENSO is 2-7 years [8,24], the research time span of fifteen years is sufficient for investigating the characteristics of ENSO. In addition, many previous studies have documented the relationships between ENSO and marine environments and gained promising results using similar time spans [13,14,19,20,22,44].…”
Section: Discussionmentioning
confidence: 98%